Characterizing and Assessing the Impact of Surgery on Healthcare Spending Among Medicare Enrolled Preoperative Super-utilizers. Issue 3 (September 2019) - Hyer, J. Madison; Ejaz, Aslam; Diaz, Adrian; Tsilimigras, Diamantis I.; Gani, Faiz; White, Susan; Pawlik, Timothy M.
Abstract : Objective: The aim of this study was to characterize preoperative super-utilizers and examine the effect of surgery on service utilization among patients undergoing major elective surgery. Summary Background Data: Rising healthcare costs are becoming increasingly burdensome for Medicare. Super-utilizers have been increasingly identified and studied as this subset of patients consume a disproportionate amount of healthcare services compared with the majority of the population. Methods: Patients aged 65 or older who underwent any of the following general elective surgeries: abdominal aortic aneurysm repair (AAA), coronary artery bypass graft (CABG), colectomy, or hip replacement were identified using 100% Medicare Inpatient and Outpatient Standard Analytic Files (SAFs) from years 2012 to 2016. Medicare inpatient and outpatient expenditures the year before surgery, around the time of surgery, and the year after surgery were examined. Results: Among 603, 105 Medicare beneficiaries, 32, 145 patients (5.3%) were categorized as super-utilizers. Compared with low-utilizers, super-utilizers were more likely to be male (low-utilizer vs super-utilizer: 47.9% vs 54.2%) and African American (4.0% vs 7.2%), whereas 58.8% (n = 208, 080) of low-utilizers presented without any comorbidity [Charlson Comorbidity Index (CCI) = 0] and 49.8% (n = 16, 007) of super-utilizers presented with a CCI score of ≥3. Total preoperative spending among super-utilizers was approximately 1.7 billion with a median of 3, 159 [interquartile range (IQR): 554–15, 181] per beneficiary. Spending among super-utilizers accounted for 39.6% of total spending for all Medicare beneficiaries versus only 8.4% among low-utilizers. Although the median spending per Medicare beneficiary in the year after surgery was higher for super-utilizers compared with low-utilizers [1, 837 (IQR: 341–11, 390) vs 18, 223 (IQR: 3, 466–43, 356)], super-utilizers accounted for 13.5% of total postoperative spending. The reduction in adjusted average annual Medicare expenditure ranged from >15, 000 per year for patients undergoing CABG to approximately 30, 000 per year for patients undergoing a hip replacement. Conclusions: Although super-utilizers accounted for only 5.3% of patients, these patients accounted for 39.6% of total Medicare expenditures in the year before surgery. Among a subset of super-utilizers, surgical intervention was associated with a reduction in annual Medicare expenditure in the year after surgery. Abstract : Supplemental Digital Content is available in the text